Targeting the BRCA1/2 deficient cancer with PARP inhibitors: Clinical outcomes and mechanistic insights - Ragupathi, Ashwin; Singh, Manrose; Perez, Alexis M.; Zhang, Dong (Frontiers in Cell and Developmental Biology, 2023)
Individuals with mutations in the BRCA1 and BRCA2 (BRCA1/2) genes, particularly women, have a significantly higher risk for developing various types of cancers, especially cancers of the breast, ovary, pancreas, and prostate. Currently, the Food and Drug Administration (FDA) has approved four PARP inhibitors (PARPi) to treat cancers with BRCA1/2 mutations. We will summarize the clinical outcomes of the four FDA approved PARPi in treating BRCA1/2 deficient cancers. We will then discuss evidence supporting the hypothesis that the cytotoxic effect of PARPi is likely due to inducing excessive replication stress at the difficult-to-replication (DTR) genomic regions in BRCA1/2 mutated tumors. The successful validation of the synthetic lethality strategy by the PARPi in the clinic has opened up new possibilities for the development of novel targeted therapy for cancer treatment. Finally, we will review additional synthetic lethal interactions with BRCA1/2 deficiency, some of which could be novel drug targets to treat BRCA1/2 mutant cancers in the near future.